The three-stage entrepreneurial model to empower recycling product designers. - Tammam, Ismail (AUC Knowledge Fountain, 2017)
Two of every five Egyptian youth aged 20-24 suffer unemployment and abject poverty. And while 40% of Egyptians have entrepreneurial intentions only 2.9% manage to establish their businesses past the 3.5-year mark of regulated operation. The main reasons for this failure have been defined to be: the poor entrepreneurial education at all stages, the poor legal &commercial infrastructure, as well as lack of supportive government programmes. The proposed solution is a three-stage process; it begins with formulating a ‘matrix model’, which is a detailed workplan for the transfer of an entrepreneurial idea from concept to a sustainable business, then developing a successful alpha product line that would allow business operation &sustenance, and then giving room for research and development of new similar products by incubating entrepreneurial ideas that can be turned into profitable product lines later on. The matrix model is the product-customised version of “Egyptian Ecosystem Theory of Change” by Saeed et al, 2015. The alpha product proposed is a flooring tile created from cleaned and shredded trash at the AUC Sustainable Development labs by heat-pressing plastics as a binder and redbrick as a filler, to create an environmentally friendly product line, then the tile is set to be tested against relevant ASTM standards for flooring tiles. Then, the proposed business model is to use part of the revenue to sponsor research and development, provided it is based on the ‘private incubator’ model. The idea is seen to positively impact the society by providing employment for the young entrepreneurs, the economy by boosting production and investment opportunities, as well as the environment by encouraging a recycling economy. This conforms with sustainable development goal number 8.6 which promotes substantially reducing the proportion of youth not in employment, education or training.